Understanding Factors Affecting UPI Adoption among Low-Income Consumers in India - Jacob, Rosin C.; Jacob, Mishel Elizabeth; Johnson, Johney (Indian Journal of Finance, 2024)
Purpose : The study investigated the factors influencing the behavioral intention to use Unified Payment Interface (UPI) apps among low-income Indian consumers. It examined how consumers’ behavioral intention to use UPI apps was influenced by their perceptions of the technology’s performance (performance expectancy), ease of use (effort expectancy), presence of facilitating conditions (FC), social influence (SI), and perceived risks (PR). Design/Methodology/Approach : An empirical study using a causal research design was conducted. The sampling unit consisted of Indian citizens with monthly household incomes below ₹ 20,000. Data were collected using questionnaires from 351 respondents and analyzed using structural equation modeling with AMOS 21. Findings : The findings demonstrated that performance expectancy, effort expectancy, and facilitating conditions positively impacted the behavioral intention to use UPI apps. A negative relationship was found between PR and behavioral intention. SI showed no impact on the usage intention among low-income consumers. Practical Implications : Understanding the adoption of UPI apps among low-income consumers can help policymakers and app developers promote financial inclusion by developing strategies to bridge the digital divide in India. Originality/Value : The study is unique as it extended the unified theory of acceptance and use of the technology model by including the PR construct in the context of UPI app adoption among the low-income population of India. Understanding this demographic is important to attaining financial inclusion.